Superconductivity and non-Fermi-liquid behavior of La3Pd4Si4 and Ce3Pd4Si4 - Kneidinger, F.; Michor, H.; Bauer, E.; Gribanov, A.; Lipatov, A.; Seropegin, Y.; Sereni, J.; Rogl, P.; Sereni, Julián (American Physical Society, 2013)
Fil: Sereni, J. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina